A educação para a cidadania global : uma experiência no 6º ano do ensino fundamental a partir do educar pela pesquisa - Costa, Camila Schwanke (2019)
Considering that the times of increasing globalization and the advent of technology have made people closer and countries mutually dependent because of economic, scientific, religious, technological, social and virtual relations, nowadays it is not enough for a human being to be a citizen of his nation-state only – who fulfills his duties and exercises his rights – but it is necessary that he becomes a global citizen, who is able to act in a fair and solidary way. While there is yet no general agreement on the idea of global citizenship, there is a common understanding that this citizenship does not concern documentation, but it refers to a sense of belonging to a broader community, to the humankind as a whole. This implies a way of looking at someone else, and of interacting in a space and time that respects diversity and pluralism. Therefore, reflections and discussions about the education we need and wish for the 21st century go through the concept of global citizenship. In addition to capacities, abilities, and cognitive knowledge, the need of an education that contributes to the solving of global challenges, and that promotes mutual respect arises. Hence, an innovative pedagogy emerges, the Global Citizenship Education (GCED), which points to the importance of an approach that goes beyond subjects and academic contents at every stage of education. This pedagogy advocates for all-round development of the person, creating opportunities to develop values and skills such as conversation, interaction, critical thinking, reflection, among other abilities in order to act ethically. With the aim of understanding the potentialities of educating through research in order to develop the education for global citizenship in basic education, this research presents the trajectory and the results of a qualitative action research carried out in a 6th year group of the Elementary School based on participant observation, text production for data collection, and textual analysis of the data collected. Based on the discursive textual analysis, the corpus was organized in an a priori category, called “Global Citizenship”, since it is the core discussion about education for global citizenship, and three a priori subcategories: ‘Citizenship’, ‘Interculturality’ and ‘Critical Thinking’, besides the emergent category called ‘Social Inequality’, this last one with a subcategory ‘Possible solutions’. The results reveal that the Global Citizenship Education Pedagogy enhances reflection, and that education through research is a possibility of instigating students to think about their own reality and to be aware that each one is responsible for and a member of glocal society (global-local). With the action research carried out and the analysis of reading and writing processes, it was possible to notice that students developed their skills and abilities proposed by CASTRO (2016), known as Diversity – Inclusion, Solidarity – Justice , Utopia – Historicity, Identity – Reflexivity dimensions. Moreover, the results indicate that even in Basic Education it is possible to work with research and project that involve education through research, and that they can foster the development of a Global Citizen.